Developments In Transparency In The Spanish Municipalities: An Analytical Revision Of The Last Research (Lex localis - Journal of Local Self-Government, 2017)
The Spanish local system rests on two pillars, municipalities and provinces. Lately, as a result of the economic crisis and the fiscal stress that afflicts most Spanish local governments they are forced to rely on inter-municipal cooperation and collaboration. This new local landscape challenges and raises concerns about accountability. Different theories confirm that working with greater transparency helps the effectiveness, efficiency and the control of corruption in the public sector and, in this context, municipalities in Spain have decided that transparency is a fertile ground that is essential to improve performance. This article, based on an analytical revision of the last research, attempts to prove that there has been substantial progress in this regard, although there is still a long road to achieving full open government.